Percutaneous iliosacral screw fixation for posterior pelvic ring injuries: the first experience, complicatons - Uvarovas, Valentinas; Vaitiekus, Andrius; Šatkauskas, Igoris; Ulevičius, Donatas (Lietuvos chirurgija, 2013)
Background Percutaneous iliosacral screw fixation is a minimally invasive technique for the treatment of unstable pelvic injuries involving the posterior ring. Nevertheless, screw malposition may result in dangerous complications involving injury to adjacent neurological structures. This study was conducted in order to evaluate the first results of using the percutaneous iliosacral screw technique at the Republican Vilnius University Hospital. Objective To report the early results and possible complications of percutaneous iliosacral screw fixation in the management of unstable pelvic ring injuries. Methods The data for the period 2011–2013 were collected retrospectively. Fifty-five patients who suffered from injury to the pelvic ring requiring surgical treatment were included in this study. Twenty-two operations were done using canulated screws (group A, 20 operations using 7.3 mm and 2 operations 8.3 mm screws), and 33 (group B) operations were done using noncanulated 6.5 mm screws. We compared our first results of using canulated and non-canulated screws. The data were analysed using MS Exel. Results From the analysed 55 patients, 20 (36.4%) were men and 35 (63.6%) women; the average age of the patients was 51 (range, 21–98) years. According to the AO (Arbeitsgemeinschaft für Osteosynthesefragen) classification, there were 49 patients with type B and 6 patients with type C. The mean operation time was 36 min (range, 10–115). Three patients from group B required reoperation because of a neurological injury. Two of these patients suffered from L5 neuropathy and one from S1 radiculalgy. The complication rate was 9.1 per cent in group B, and they were now complicationa in group B. Twelve patients underwent percutaneous iliosacral screw fixation and anterior fixation, one patient underwent percutaneous iliosacral conversion to open posterior SI fixation osteosynthesis because of neurological complications, while the other 43 patients underwent percutaneous screw fixation only. Conclusions Percutaneous iliosacral screw fixation is a rapid, safe and definitive treatment for unstable pelvic ring injury. The technique using standard C-arm fluoroscopy may allow accurate location of the screw placed in S1 and result in fewer complications when using percutaneous canulated screws. Key words: percutaneous iliosacral fixation, canulated iliosacral screws, three-dimensional fluoroscopy Perkutaninė kryžkaulio klubikaulio sąnario fiksacija esant užpakalinio dubens žiedo sužalojimams: pirmoji patirtis, komplikacijos Įvadas / tikslas Perkutaninė kryžkaulio klubakaulio sąnario fiksacija sraigtais yra minimaliai invazinis operacinio gydymo metodas nestabiliems užpakalinio dubens žiedo sužalojimams gydyti. Vis dėlto gretimos nervinės struktūros gali būti pažeistos dėl blogos sraigto padėties. Mūsų darbo tikslas – įvertinti Respublikinės Vilniaus universitetinės ligoninės pirmuosius kryžkaulio klubikaulio sąnario operacinio gydymo perkutaninės fiksacijos būdu rezultatus ir nustatyti nestabilių dubens žiedo sužalojimų gydymo komplikacijų dažnį. Metodai Retrospektyviai išanalizuoti 2011–2013 metais gydytų 55 pacientų duomenys. Atliktos 22 operacijos naudojant kaniuliuotus (A grupė, 20 operacijų naudojant 7,3 mm ir 2 operacijos 8,3 mm sraigtus) ir 33 (B grupė) – nekaniuliuotus 6,5 mm sraigtus. Palyginome pirmuosius operacinio gydymo kaniuliuotais ir nekaniuliuotais sraigtais rezultatus. Duomenys analizavome MS Exel programa. Rezultatai Operuoti 55 pacientai, iš jų 20 (36,4 %) vyrų ir 35 (63,6 %) moterys. Tiriamųjų amžiaus vidurkis – 51 (21–98) metai. Pagal AO (Arbeitsgemeinschaft für Osteosynthesefragen) klasifikaciją buvo 49 pacientai. Trys B grupės (9,1 %) pacientai buvo peroperuoti dėl neurologinių komplikacijų (du pacientai dėl L5 neuropatijos ir vienas dėl S1 radikulialgijos). A grupės pacientams komplikacijų nebuvo. Dvylikai pacientų atlikta perkutaninė kryžkaulio klubakaulio sąnario fiksacija ir kartu priekinė fiksacija ir 43 pacientams – tik užpakalinė kryžkaulio klubakaulio sąnario fiksacija sraigtu. Išvados Perkutaninė kryžkaulio klubakaulio sąnario fiksacija yra greitas, saugus ir galutinis nestabilių užpakalinio dubens žiedo sužalojimų operacinio gydymo metodas. Naudojant standartinį rentgeno C-lanką galima tiksliai lokalizuoti sraigto padėtį S1 slankstelio lygyje. Naudojant kaniuliuotus sraigtus komplikacijų nepasitaikė, o naudojant nekaniuliuotus sraigtus galimos neurologinės komplikacijos. Reikšminiai žodžiai: perkutaninė kryžkaulio klubakaulio sąnario fiksacija, kaniuliuoti kryžkaulio klubakaulio sraigtai, trijų dimensijų fluoroskopija.